2017
DOI: 10.1039/c6ra27542g
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity and mechanism of heat-transformed ginsenosides from notoginseng against Epidermophyton floccosum, Trichophyton rubrum, and Trichophyton mentagrophytes

Abstract: The improved antifungal activity of notoginseng can be attributed to the formation of less polar ginsenosides by heat transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The structure of ginsenosides might affect the antimicrobial activity. In recent studies (Wang et al, ; Xue, Yang, et al, ; Xue, Yao, et al, ), polar ginsenosides, such as Rg 3 , Rg 6 , F 4 , Rg 5 , Rk 1 , Rs 3 , Rk 3 , Rh 2 , Rh 4 , and Rh 5 exhibited better antimicrobial effects than Re, Rg 1 , Rb 2 , Rc, and Rd, which are natural‐occurring ginsenosides. Our review might facilitate and guide further studies needed to optimize the use of ginseng and their components to improve microbial food safety and prevent or treat animal and human infections.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The structure of ginsenosides might affect the antimicrobial activity. In recent studies (Wang et al, ; Xue, Yang, et al, ; Xue, Yao, et al, ), polar ginsenosides, such as Rg 3 , Rg 6 , F 4 , Rg 5 , Rk 1 , Rs 3 , Rk 3 , Rh 2 , Rh 4 , and Rh 5 exhibited better antimicrobial effects than Re, Rg 1 , Rb 2 , Rc, and Rd, which are natural‐occurring ginsenosides. Our review might facilitate and guide further studies needed to optimize the use of ginseng and their components to improve microbial food safety and prevent or treat animal and human infections.…”
Section: Discussionmentioning
confidence: 97%
“…Notoginseng RNase displayed in vitro antifungal activity against Coprinus comatus and Physalospora piricola (Lam & Ng, ). Another research, conducted by Xue, Yang, et al, , found that (a) less polar ginsenosides fraction heat‐transformed ginsenoside containing 70.7% of Rk 3 , Rh 4 , and Rh 5 (Figure ) obtained from heat transformation of notoginseng saponin NS (containing 79.1% of R1, Rg 1 , Re, Rb 2 , and Rd) showed strong antifungal effect against Epidermophyton floccosum , Trichophyton rubrum , and Trichophyton mentagrophytes with an MIC value of 31.25, 16.00, and 31.25 μg/ml, respectively; (b) the ginsenoside monomers Rk 3 , Rh 4 , and Rh 5 have stronger antifungal activity than that of R 1 , Rg 1 , Re, Rb 2 , and Rd; (c) the antifungal mechanism of heat‐transformed ginsenoside might be attributed to the damage of cell membrane and decrease of membrane potential; and (d) the antifungal activity of individual ginsenosides was negatively correlated with the number of their sugar moieties. Ginsenoside‐enriched fraction isolated from red Asian ginseng, in an MIC value of 50–100 μg/ml, exerted considerable antifungal activities against Saccharomyces cerevisiae, Trichosporon beigelii, and Candida albicans by disrupting the structure of the cell membrane (Sung and Lee 2008).…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…interdigitale ATCC 9533. 33 The fungal suspension was then diluted to 5% v/v of the potato dextrose broth. Kaffir lime oil, or citronellal, was dissolved to an initial concentration of 4% v/v in 2% DMSO in the potato dextrose broth.…”
Section: Broth Macrodilution Methods For the Determination Of Kaffir Lmentioning
confidence: 99%
“…The examined methods were the minimum inhibitory concentrations (MICs) [22], minimum bactericidal concentration (MBCs) or minimum fungicidal concentration (MFCs) [32,33] and zone of inhibitions (ZOIs) [34]. ZOI is qualitative analysis and MIC is quantitative analysis of antimicrobial activity [35].…”
Section: Antimicrobial Activitymentioning
confidence: 99%